Prophet Muhammad's Communication Strategy Perspective of Tafsir Maudu'i al- Wajiz - Zulaiha, Eni (International Journal of Nusantara Islam, 2024)
This article aims to identify the communication strategy of the Prophet Muhammad as described in the Qur'an. This study used qualitative methods through library research. Thematic interpretation was used as the analytical technique. The results indicate that the Prophet's communication principles are as follows: First, using striking words (qawlan balīghā). Second, we selected easily digestible words (qawlan maysūrā). Third, noble words (qawlan karīmā) were used. Fourth are constructive words (qawulan ma'rūfā). Fifth, using gentle words (qawulan layyinā). The Prophet's communication strategy prioritizes deliberation in solving problems. The conclusion from the research proves that the principles and communication strategies of the Prophet Muhammad in conveying God's message, as outlined in the Qur'an, are essential elements for the success of his mission. This study recommends further research on other critical elements supporting the success of prophetic preaching based on Quranic verses